Salmonella enterica serovar Typhi osteomyelitis in a young adult with sickle cell and thalassemia traits: A possible association. (2019) - Stephanie, Stephanie; Schmalzle, Sarah A.
Abstract: Salmonella osteomyelitis is known to occur in immunocompromised and sickle cell disease patients. It rarely occurs in other hosts. We present a case of chronic femoral osteomyelitis due to S. enterica serovar Typhi seen in a Maryland resident. Potential risk factors included traveling to an endemic area as well as a newly diagnosed sickle cell trait and thalassemia trait. It is postulated that less severe hemoglobinopathies may also contribute to an elevated risk of Salmonella osteomyelitis.